Minimally invasive intervention for infected necrosis in acute pancreatitis. (November 2014) - Hollemans, Robbert A; van Brunschot, Sandra; Bakker, Olaf J; Bollen, Thomas L; Timmer, Robin; Besselink, Marc GH; van Santvoort, Hjalmar C
<x xml:space="preserve">Abstract</x> Infected necrosis is the main indication for invasive intervention in acute necrotizing pancreatitis. The 2013 IAP/APA guidelines state that percutaneous catheter drainage should be the first step in the treatment of infected necrosis. In 50–65% of patients, additional necrosectomy is required after catheter drainage, which was traditionally done by open necrosectomy. Driven by the perceived lower complication rate, there is an increasing trend toward minimally invasive percutaneous and endoscopic transluminal necrosectomy. The authors present an overview of current minimally invasive treatment options for necrotizing pancreatitis and review recent developments in clinical studies.